2006
DOI: 10.1007/s10562-006-0140-9
|View full text |Cite
|
Sign up to set email alerts
|

Nano-sized crystallites of vanadyl pyrophosphate as a highly selective catalyst for n-butane oxidation

Abstract: Exfoliation-reduction of VOPO 4 AE 2H 2 O in a mixed alcohol consisting of 2-butanol and ethanol, followed by the thermal treatment in the presence of n-butane, O 2 , and He at 663 K for 300 h, produces novel nano-sized crystallites ($50 nm) of (VO) 2 P 2 O 7 . The nano-sized (VO) 2 P 2 O 7 crystallites exhibit a high selectivity to maleic anhydride ($84%) for the selective oxidation of n-butane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…We previously succeeded in carrying out exfoliation of VOPO 4 ·2H 2 O in various alcohols [13], and demonstrated that subsequent reduction of the exfoliated VOPO 4 sheets with alcohol produced VOHPO 4 ·0.5H 2 O. In particular, as we described in a preliminary report [14], (VO) 2 P 2 O 7 catalyst derived from VOHPO 4 ·0.5H 2 O which had been prepared by exfoliation-reduction of VOPO 4 ·2H 2 O in a mixed alcohol solvent (2-butanol and ethanol) was found to be superior, in terms of activity and selectivity, to the catalyst derived from VOHPO 4 ·0.5H 2 O prepared in 2-butanol alone and by the direct-reduction method for n-butane oxidation [15].…”
Section: Introductionmentioning
confidence: 73%
“…We previously succeeded in carrying out exfoliation of VOPO 4 ·2H 2 O in various alcohols [13], and demonstrated that subsequent reduction of the exfoliated VOPO 4 sheets with alcohol produced VOHPO 4 ·0.5H 2 O. In particular, as we described in a preliminary report [14], (VO) 2 P 2 O 7 catalyst derived from VOHPO 4 ·0.5H 2 O which had been prepared by exfoliation-reduction of VOPO 4 ·2H 2 O in a mixed alcohol solvent (2-butanol and ethanol) was found to be superior, in terms of activity and selectivity, to the catalyst derived from VOHPO 4 ·0.5H 2 O prepared in 2-butanol alone and by the direct-reduction method for n-butane oxidation [15].…”
Section: Introductionmentioning
confidence: 73%
“…Thus, the observed gain in n-butane conversion and maleic anhydride selectivity had been attributed to the good reducibility and oxidizibility of the (VO) 2 P 2 O 7 catalyst [15,16,18]. Apart from the above matters pertaining to the performance of VPO catalysts, a number of factors can influence its performance such as its preparative route, starting material type for preparations, detailed phase composition and reaction medium [19][20][21][22]. The (VO) 2 P 2 O 7 phase is obtained from VOHPO 4 Á0.5H 2 O precursor that is transformed under reaction conditions (n-butane/O 2 flow, 400°C) or calcination in N 2 at 550°C [19].…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting point to note is that, by changing the solvent from 2-butanol to isobutanol in the intercalation and exfoliation stage, the (001), (101), (021), and (121) appeared to be less intense and broader as compared to those catalysts precursor that using 2-butanol as solvent in the mentioned stage above. erefore, this also indicated that using isobutanol instead of 2-butanol as solvent in the intercalation and exfoliation stage somehow promotes the formation of more amorphous VPD precursor compared to the VPD precursor that used 2-butanol as solvent in the intercalation and exfoliation stage which has been well studied by Kamiya and coworkers [11]. Figure 2 exhibited the XRD patterns of intercalationexfoliation-reduction VPD catalysts, aer being activated at 733 K in reaction environment (0.75% n-butane/air mixture) for 18 h. All the catalysts produced are very similar and show the characteristic of (VO) 2 P 2 O 7 phase with (020), (204), and (221) lines at 22.9 ∘ , 28.4 ∘ , and 29.9 ∘ , respectively.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 79%